A first-principles study of Cu and Al doping in ZrO2 for RRAM device applications. (October 2019) - Hussain, Fayyaz; Imran, Muhammad; Khalil, R.M. Arif; Sattar, M. Atif; Niaz, Niaz Ahmad; Rana, Anwar Manzoor; Ismail, Muhammad; Khera, Ejaz Ahmad; Rasheed, Umbreen; Mumtaz, Faqeeha; Javed, Tariq; Kim, Sungjun
Abstract: First-principle calculations were carried out to calculate formation energy, charge density and electronic properties of doped ZrO2 with and without single oxygen vacancy (Vo ) using density functional theory (DFT). Increasing concentration of Al dopant without Vo decreased the conductivity of the system (ZrO2 ) and vice versa in case of Cu dopant. Isosurface charge density plots confirmed that conducting channels were created in both cases in addition to that Al dopant with Vo improved the conductivity and enhanced conducting channel. The ZrO2 doped with Cu formed conducting channel (metal ions) and enhanced the conductivity, while Cu with Vo was less conductive with shortened conducting channels. These results showed impacts of dopants (metal ions) with and without oxygen vacancy to increase the efficiency of non-volatile RRAM devices. Electronic properties confirmed that ZrO2 with substitutional doping of Al having Vo was comparatively better electrode material for RRAM technology while Cu without Vo. These studies showed that ZrO2 based RRAM devices have an excessive potential for future memory applications. Highlights: Doping of Al and Cu in ZrO2 bulk for the designing of highly efficient RRAM devices. Al dopant with Vo improved the conductivity and enhanced conducting channels. ZrO2 doped with Cu having Vo was less conductive with shortened conducting channels. ZrO2 with substitutional doping of Al having Vo is comparatively better electrode material for RRAM technology.